PELAKSANAAN DENDA TILAGNG PROGRESIF MELALUI ELECTRONIC TRAFFIC LAW ENFORCEMENT (E-TLE) PADA PELANGGARAN LALU LINTAS - Jalal, Abdul; Ramadhani, Muh. Yassir Akbar (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2025)
Abstract : Along with increasingly sophisticated technological advances, the Indonesian National Police has achieved proud achievements by implementing a system known as ETLE (Electronic Traffic Law Enforcement). Through the ETLE mechanism, violators who are proven guilty will be subject to fines as regulated in Law Number 22 of 2009. This research examines the implementation of ETLE penalties by Law Number 22 of 2009 concerning Road Traffic and Transportation. The method used is Normative Research with a statutory approach using the legal framework and conceptual framework of Law Number 22 of 2009 concerning Road Traffic and Transportation. The research results show that enforcement of Law Number 22 of 2009 in Indonesia significantly increases the safety of road users and improves traffic quality. Through a comprehensive approach and cross-sectoral collaboration, it is hoped that a positive, safe, orderly, and law-abiding traffic culture can be realized in society, by the mandate of Law Number 22 of 2009 concerning Road Traffic and Transportation which confirms that ETLE is a form of law enforcement against traffic violations carried out by the police.